Relationships between addiction and the COMT rs4680 Gene Polymorphism: Hubungan antara kecanduan dan Polimorfisme Gen COMT rs4680 - Wael Sattar Jaber; Fulla Abd Alsattar Alriyahee (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: Addiction to drugs and alcohol is a complex neuropsychiatric disorder influenced by both environmental and genetic factors, particularly those affecting dopamine regulation. Specific Background: The catechol-O-methyltransferase (COMT) gene, particularly the rs4680 Val158Met polymorphism, plays a crucial role in dopamine metabolism and has been implicated in addiction susceptibility. Knowledge Gap: While several studies link COMT variants to substance use disorders, evidence from Middle Eastern populations, especially Iraq, remains limited. Aims: This study aimed to assess the association between the COMT rs4680 polymorphism and vulnerability to drug and alcohol addiction in an Iraqi male cohort. Results: Analysis of 90 samples revealed a significantly higher frequency of the A allele and AA genotype in addicts compared to controls. The AA genotype was associated with a 14.55-fold and 17.14-fold increased risk of drug and alcohol addiction, respectively, while the GA genotype showed intermediate risk. Novelty: This is among the first studies to examine this genetic association in an Iraqi context, highlighting the contribution of COMT polymorphism to addiction predisposition. Implications: The findings suggest potential for genetic screening and personalized intervention strategies targeting dopaminergic pathways in addiction prevention and treatment.Highlight : The A allele of the rs4680 polymorphism is significantly associated with increased addiction risk. The AA genotype shows a strong correlation with both drug and alcohol addiction. The GA genotype indicates moderate vulnerability to addictive behavior. Keywords : rs4680 Polymorphism, COMT Gene, Addiction, Drug Use, Alcohol Use